2021
DOI: 10.1177/13524585211047223
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy and safety of inebilizumab in neuromyelitis optica spectrum disorder: Analysis of aquaporin-4–immunoglobulin G–seropositive participants taking inebilizumab for ⩾4 years in the N-MOmentum trial

Abstract: Background: Efficacy and safety of inebilizumab for treatment of neuromyelitis optica spectrum disorder in adults seropositive for aquaporin-4 (AQP4)–immunoglobulin (Ig) G were demonstrated in the 28-week randomized controlled period of the N-MOmentum study. Objective: To assess efficacy and safety of long-term inebilizumab treatment. Methods: Post hoc analysis was performed in 75 AQP4–IgG–seropositive participants receiving inebilizumab for ⩾4 years in the randomized controlled period and open-label extension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 10 publications
(24 reference statements)
0
32
0
Order By: Relevance
“…For ofatumumab, postinjection systemic inflammatory reactions can occur but are very mild and generally do not require pretreatment. The depletion of circulating B cells also leads to risk of infection, and some studies, 8 though not all, 9 suggest that this can arise particularly in the setting of hypogammaglobulinemia. In addition to IgG depletion, depletion of IgM and IgA can also occur 10 (vide infra, section on breastfeeding).…”
Section: Use Of B-cell Depletion In Ms and Nmosdmentioning
confidence: 99%
“…For ofatumumab, postinjection systemic inflammatory reactions can occur but are very mild and generally do not require pretreatment. The depletion of circulating B cells also leads to risk of infection, and some studies, 8 though not all, 9 suggest that this can arise particularly in the setting of hypogammaglobulinemia. In addition to IgG depletion, depletion of IgM and IgA can also occur 10 (vide infra, section on breastfeeding).…”
Section: Use Of B-cell Depletion In Ms and Nmosdmentioning
confidence: 99%
“…Just as CLP can be used to deplete microglia and macrophage populations, it is also possible to deplete immunoglobulin-producing plasmacytes. For example, inebilizumab, a monoclonal antibody (mAb), binds to and depletes CD19 + B cells, including plasmablasts and plasmacytes [ 28 ], leading to immunoglobulin depletion.…”
Section: Discussionmentioning
confidence: 99%
“…Inebilizumab treatment in NMOSD patients induced a robust depletion of CD20-positive B cells, that was maintained for at least 4 years ( 76 ). In a phase I study on 21 MS patients treated with different doses of inebilizumab, rapid B-cell depletion was observed at all dosing regimens except the 60-mg subcutaneously dose; the extent and duration of the B-cell depletion were dose-dependent, with most dose groups maintaining 90% depletion throughout the 24-week follow-up period ( 40 ).…”
Section: Effect Of Cell Depleting-abs On Adaptive Immune Signatures I...mentioning
confidence: 99%
“…As an unwanted on-target effect, concentrations of IgG, IgM, IgA, and IgE decreased over time during treatment with inebilizumab. Most participants (76%) maintained normal IgG levels, and no significant associations were observed between the lowest reported IgG categories and severe infections, although the relatively small number of the participants could have prevented from finding significant correlations ( 76 ). In a phase I study on MS patients, total Ig levels at week 24 showed a mean percentage decrease of 10.5% from baseline, rising to 15.0% at the 18-month follow-up ( 40 ).…”
Section: Effect Of Cell Depleting-abs On Adaptive Immune Signatures I...mentioning
confidence: 99%
See 1 more Smart Citation